PENGGUNAAN METODE PEMBERIAN TUGAS BELAJAR PADA SISWA KELAS V UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR BIDANG STUDI AGAMA ISLAM DI SDN JENGGAWAH 07 KECAMATAN JENGGAWAH JEMBER SEMESTER GANJIL TAHUN 2012/2013 - Hasan Al Haris (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2014)
As previously described, the research problems in this study can be formulated as follows: (1)Is the implementation of the method of administration tasks on the learning of PAIfor the students of SDN Jenggawah 07, odd semester of academic year 2012/2013, able to improve the learning activities and students’ outcomes?; and (2) How does the implementation of the method of administration task on the learning of PAI for the students of SDN Jenggawah 07, odd semester of academic year 2012/2013, improve the learning activities and students’ outcomes? In accordance with those research problems, this study thus aims to: (1) Describe the learning activity and students’ outcomes increased by using the method of administrationtasks on thelearning of PAI for the students of SDN Jenggawah 07, odd semester of academic year 2012/2013; and (2) Describe the implementation of the method of administration task on the learning of PAI for the students of SDN Jenggawah 07, odd semester of academic year 2012/2013; improve the students’ learning activities and outcomes.  The researcherhas conducteda clasroom actionresearch (CAR). The subject of this study is the fourth grader students of SDN Jenggawah 07. Method of collecting tyhe data in this study are observation, test, interview, and questionnaire. Descriptive qualitative is employed to analyze the data.  The research findings show: (1) the students’ main score of pretest was 63, (2) the students’ main score of cycle I was 78, (3) the students’ main score of cycle II was 100.Keywords: Learning activities, Learning outcomes, Administrative task method, PAI.